2017
DOI: 10.1115/1.4036583
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Enumeration of Feasible Kinematic Diagrams for Split Hybrid Configurations With a Single Planetary Gear

Abstract: Most of the prior studies on power-split hybrid electric vehicle's (PS-HEV) design focused on the powertrain configuration optimization. Yet, depicting the selected configuration is highly required for further design steps, ultimately manufacturing. This paper proposes an automatic approach to generate all the feasible kinematic diagrams for a given configuration with a single planetary gear (PG) set. While the powertrain configuration, which is the output of prior studies, illustrates the connection of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…And the yaw stability of the vehicle is not considered. The driving force F out , driving torque T out and the speed of output shaft ω out for the vehicle are shown in Equations (10) and (11).…”
Section: Parameter and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…And the yaw stability of the vehicle is not considered. The driving force F out , driving torque T out and the speed of output shaft ω out for the vehicle are shown in Equations (10) and (11).…”
Section: Parameter and Modelmentioning
confidence: 99%
“…By introducing clutch to change the way of combination and connection between PG nodes and power resource components, the power-split hybrid powertrain configuration possesses multiple operating modes, which greatly increases the probability of high-efficient operation for the vehicle. Therefore, the multi-mode power-split hybrid powertrain configuration based on planetary gear (PG) has enormous potential in improving fuel economy [10,11]. However, the flexible combination and connection of PG lead to a large number of configuration candidates, which make it difficult to simultaneously express the topology and functional characteristics and judge the feasibility and applicability of configurations.…”
Section: Introductionmentioning
confidence: 99%
“…its kinematic diagrams are generated). In fact, the kinematic diagrams are required not only to check its possible realization, but also to verify the physical constraints [37]. The systematic generation of feasible kinematic diagrams for compoundsplit hybrid configurations is the future work of this study.…”
Section: Comparative Analysis Of Selected Configurationsmentioning
confidence: 99%
“…Shanmukhasundaram et al [18] applied the concept of kinematic unit in the representation method of rotation and displacement graphs to synthesize EGTs with up to 7 links. Moreover, scholars [19][20][21] focused on the configurations synthesis of ATs, which is normally used for hybrid electric vehicles. It should be indicated that these devices are expected to play an important role in the energy and environmental conservations in the near future.…”
Section: Introductionmentioning
confidence: 99%